Cockscomb-shaped twighopper, Cladonotus bhaskari sp. n., a new and rare pygmy grasshopper species from Sri Lanka (Orthoptera: Tetrigidae: Cladonotinae) - Tumbrinck, Josef; Deranja, Maks; Adžić, Karmela; Pavlović, Marko; Skejo, Josip (Zootaxa, 2020)
The paper describes a new species of a Sri Lankan twighopper, genus Cladonotus Saussure, 1862 (Orthoptera: Tetrigidae: Cladonotini), C. bhaskari sp. n., based on a single female specimen collected and photographed by T. Kirschey in 2016 in Sinharaja rainforest (SW Sri Lanka). The new species is clearly distinguished from other species of the genus by its long and spine-like frontomedial projection and cockscomb-shaped promedial projection. Species of this genus resemble tiny twigs, hence the name ‘twighopper’. Our new specimen is the first known female of the genus, and we also present the first photograph of the member of this genus in the natural habitat. An annotated identification key for the Cladonotus species is provided. Furthermore, we synonymize genus Hypsaeus Bolívar, 1887 syn. nov. with Hymenotes Westwood, 1837, based on the pronotal variability of the leaf-like pygmy grasshoppers in the Philippines and introduce one new combination—Hymenotes westwoodi (Bolívar, 1887) comb. nov..